Volume 2A: Turbomachinery 2014
DOI: 10.1115/gt2014-26099
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization of the Effect of Axial Positioning of Bend Skewed Casing Treatment Retrofitted to a Transonic Axial Flow Compressor

Abstract: The performance of an aero-engines to a large extend depends on the performance behavior of axial flow compressors and is restricted by the compressor instabilities like rotating stall and surge. In the present study, attempts have been made to design and develop the bend skewed casing treatment geometries with lower porosities to improve the stable operating range of single stage axial flow compressor. Experimental investigations were undertaken to study the impact of axial position of one of the casing treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The former believed that too small overlap amount resulted in the loss of stability expansion ability, while the latter came to the conclusion that the best stability expansion effect was obtained with 33% overlap amount. Alone et al 19 and Zhang et al 20 respectively conducted research on the position and porosity of axial slot. Furthermore, Ba et al 21 adopted genetic algorithm to optimize three kinds of axial slot with different meridional shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The former believed that too small overlap amount resulted in the loss of stability expansion ability, while the latter came to the conclusion that the best stability expansion effect was obtained with 33% overlap amount. Alone et al 19 and Zhang et al 20 respectively conducted research on the position and porosity of axial slot. Furthermore, Ba et al 21 adopted genetic algorithm to optimize three kinds of axial slot with different meridional shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that when the slot is located at the initial position of the tip leakage vortex and the boundary layer separation region downstream of the shock wave, the stall margin improvement is maximum. Alone et al (Alone et al, 2014(Alone et al, , 2017carried out a parametric experimental study on the bend skewed casing treatment, including the depth and volume of the plenum chamber, the axial position, and the porosity. The results show that the curved inclined casing treatment with 20 to 40% axial position and 33% porosity can improve the stall margin and improve the compressor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 14 discussed the effect of the position of the circumferential groove on the performance of a transonic rotor, and the results manifested that when the groove is located at the initial position of the TLV and the boundary layer separation region downstream of the shock wave, its stabilization ability is maximum. A parametric study of bend skewed casing treatment was carried out by Alone et al 15,16 The results showed that the curved inclined casing treatment with 20%-40% axial position and 33% porosity can improve the stall margin and improve the compressor efficiency. Inzenhofer et al 17 compared the difference between the axial slot casing treatment (ASCT) and the selfrecirculating casing treatment.…”
Section: Introductionmentioning
confidence: 99%